Conformation and Cross-Protection in Group B Streptococcus Serotype III and Streptococcus pneumoniae Serotype 14: A Molecular Modeling Study - Michelle M. Kuttel; Neil Ravenscroft (MDPI AG, 2019)
Although the branched capsular polysaccharides of Streptococcus agalactiae serotype III (GBSIII PS) and Streptococcus pneumoniae serotype 14 (Pn14 PS) differ only in the addition of a terminal sialic acid on the GBSIII PS side chains, these very similar polysaccharides are immunogenically distinct. Our simulations of GBSIII PS, Pn14 PS and the unbranched backbone polysaccharide provide a conformational rationale for the different antigenic epitopes identified for these PS. We find that side chains stabilize the proximal <semantics> β </semantics> dGlc(1→6) <semantics> β </semantics> dGlcNAc backbone linkage, restricting rotation and creating a well-defined conformational epitope at the branch point. This agrees with the glycotope structure recognized by an anti-GBSIII PS functional monoclonal antibody. We find the same dominant solution conformation for GBSIII and Pn14 PS: aside from the branch point, the backbone is very flexible with a “zig-zag„ conformational habit, rather than the helix previously proposed for GBSIII PS. This suggests a common strategy for bacterial evasion of the host immune system: a flexible backbone that is less perceptible to the immune system, combined with conformationally-defined branch points presenting human-mimic epitopes. This work demonstrates how small structural features such as side chains can alter the conformation of a polysaccharide by restricting rotation around backbone linkages.